A comparison of effectiveness between oral rapid testing and routine serum-based testing for HIV in an outpatient dental clinic in Yuxi Prefecture, China: a case–control study. Issue 6 (30th June 2017) - Li, Shifu; Su, Shu; Li, Shunxiang; Gao, Liangmin; Cai, Ying; Fu, Jincui; Guo, Chunyuan; Lu, Wei; Cheng, Feng; Jing, Jun; Chen, Liang; Zhang, Lei
Abstract : Objective: To compare the outcomes of routine provider-initiated HIV testing and counselling (PITC) and oral rapid HIV testing for dental clinic outpatients in a hospital. Design: We employed a case–control study design and recruited dental outpatients into routine serum-based and oral rapid testing groups. We compared the acceptance, completion and result notification rate between groups. Setting: A dental outpatient clinic in the Yuxi People's Hospital, Yunnan. Participants: A total of 758 and 816 dental outpatients were enrolled for routine and oral rapid testing, respectively. Results: The percentage of participants willing to receive routine HIV testing was 28.1% (95% CI 24.9% to 31.3%) and 96.1% (95% CI 94.8% to 97.4%, χ2 =186.4, p<0.001) for the rapid testing. Among accepted participants, the percentage of participants who received HIV testing was 26.8% (95% CI 20.9% to 32.7%) in the routine testing group and 100.0% in the oral rapid HIV testing group ( χ2 =77.5, p<0.001). About 93.0% of routine testers returned for the test results on the next day, whereas all rapid testers received their test results on the same day ( χ2 =34.6, p<0.001). These correspond to an overall completion rate of 7.0% (95% CI 5.2% to 8.8%) and 96.1% (95% CI 94.8% to 97.4%, p<0.001), respectively. Among the 545 patients who declined routine serum-based HIV testing, the main reasons included, an unnecessary hassle (254/545, 46.6%), having been previously tested (124/545, 22.8%) and self-perceived low risk of HIV infection (103/545, 18.9%). In contrast, only 32 individuals declined oral rapid testing, and having received a previous test was the primary reason. Three patients in the rapid testing group were later confirmed HIV-positive, yielding an HIV prevalence of 0.38%. Conclusion: Oral rapid HIV testing is a feasible and efficient approach in a clinical setting.